1995
DOI: 10.1897/1552-8618(1995)14[303:pcahbs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

PCB Congeners and Hexachlorobenzene Biota Sediment Accumulation Factors for Macoma Nasuta Exposed to Sediments With Different Total Organic Carbon Contents

Abstract: Deposit‐feeding marine clams (Macoma nasuta) were exposed for 119 d to three sediment types that varied in total organic carbon (TOC) from 0.8 to 2.5%. Sediments were spiked with equal concentrations of 13 polychlorinated biphenyl congeners and hexachlorobenzene. Tissue residues were measured, and steady‐state bioaccumulation factors (BAFs), the corresponding lipid, and TOC‐normalized biota sediment accumulation factors (BSAFs) were determined. The BSAFs were less variable than were the BAFs with the exception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
4
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(107 citation statements)
references
References 11 publications
5
97
4
1
Order By: Relevance
“…This, in turn, projected a lower time to steady state. The rates of elimination and time to steady state of PCBs in M. nasuta derived for the Arthur Kill sediment exposure more closely agree with those previously reported by Boese et al (1995Boese et al ( , 1997.…”
Section: Relationship To K Owsupporting
confidence: 88%
See 4 more Smart Citations
“…This, in turn, projected a lower time to steady state. The rates of elimination and time to steady state of PCBs in M. nasuta derived for the Arthur Kill sediment exposure more closely agree with those previously reported by Boese et al (1995Boese et al ( , 1997.…”
Section: Relationship To K Owsupporting
confidence: 88%
“…An additional study by Drouillard et al (2008) For N. virens, the 28-d and steady-state BSAFs were similar among congeners and between the Arthur Kill and Newark Bay sediment exposures ( Figure 16). The BSAFs obtained in this study were lower overall compared to previously reported values (0.19-1.41) (Pruell et al 1993 Ferraro et al 1990Ferraro et al , 1991Brannon et al 1993;Pruell et al 1993;Boese et al 1995Boese et al , 1996. Overall, the BSAFs obtained in this study for M. nasuta were lower compared to previously reported values.…”
Section: Polychlorinated Biphenyls (Pcbs)contrasting
confidence: 87%
See 3 more Smart Citations